Y > x
y = 2(3+x)
y = 3x-2
------------------------------
2(3+x) = 3x-2
2(3+x) - (3x-2) = 0
6 + 2x -3x + 2 = 0
8 -x = 0
x = 8
---------------------------
y = 2(3+x) = 2(3+8) = 22
y = 3x-2 = 3*8 -2 = 22
----------------------------------
x = 8 ; y = 22
Answer:6m
Step-by-step explanation:
Square root 36m²
No
I think that’s it(sorry if I’m wrong)
Answer:
x = -9
Step-by-step explanation:
4x+10=-26
Subtract 10 from each side
4x+10-10=-26-10
4x = -36
Divide each side by 4
4x/4 = -36/4
x = -9
Answer:
Step-by-step explanation:
In japan the average cost is up from $.1200 in some change to
in Switzerland the average cost is 15.00 and some change